A new Acartophthalmites Hennig from Eocene Baltic amber (Diptera, Acalyptratae) - Ricardo Pérez-de la Fuente; Christel Hoffeins; Jindřich Roháček (ZooKeys, 2018)
A new fossil fly species, Acartophthalmites willii sp. n. (Diptera: Acalyptratae: Opomyzoidea) from Baltic amber (Eocene, 56−33.9 Ma), is described based on a male originally assigned by Hennig (1969) to A. tertiaria Hennig, 1965, who erroneously also referred to it in the same work as “A. electrica Hennig” (unavailable name). The new species, representing the third named species of the extinct genus with unclear familial relationships Acartophthalmites Hennig, 1965, is herein described and illustrated in detail, and its systematic implications and relationships are discussed. From the morphological standpoint, the new species represents an intermediate form between the two formerly described species within the genus, therefore expanding the character combination diversity in this lineage of acalyptrate flies. The genus Acartophthalmites is considered to be most closely related to Clusiidae and, therefore, it is herein tentatively classified within the superfamily Opomyzoidea. The current work takes part of an effort to review the Acartophthalmites diversity in order to gain knowledge on the morphological data from the specimens described within the genus and ultimately enable a reliable analysis of its phylogenetic relationships with other acalyptrates.